Anti-bacterial and cytotoxicity properties of the leaves extract of nahar (Mesua Ferrea) plant - Adewale, Ahmed Idris; Mirghani, Mohamed Elwathig Saeed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Abimbola, Mikail Maryam (American-Eurasian Network for Scientific Information, 2012)
The increasing bacterial resistance to antibiotics and the growing interest in human health have resulted into an increasing need for the exploration of both the essential oils and other plant extracts in the food and pharmaceutical industries. This work, as part of on-going work on the leaves of Nahar (Mesua ferrea) plant, was aimed at evaluating the antibacterial activity, minimum inhibitory concentration as well as the cytotoxicity of the leaves extract. The dry leaves were grinded and extracted in an oven shaker set at 37°C and 200rpm for 24 hours using ethanol and methanol as solvents. The agar disc diffusion method was used for the evaluation of antibacterial property of the leaves extract, micro broth dilution was employed for the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), while Brine shrimp (Artemia salina) lethality bioassay was made use of for the cytotoxicity assay. Ethanol gave higher extract’s yield (6.20%) than methanol. The extract showed a remarkable antibacterial property against all the selected microbes (Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus) with the inhibition zones ranging from 16.0±0.5 mm to 18.0±0.5 mm for all the tested bacteria. The MIC range of 2.5- 0.625 mg/mL with MBC value of 5 mg/mL was obtained for the gram-negative bacteria while MIC range of 1.3- 0.313 mg/mL with MBC value of 2.5 mg/mL was obtained for the gram-positive bacteria. The leaves extract was found to be toxic to the Brine shrimps with LC50 of 500ppm (μg/mL) suggesting that the extracts may contain bioactive compounds of potential therapeutic and prophylactic significance